2021
DOI: 10.1074/jbc.ra120.015867
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and characterization of the 5′ exonuclease activity of the lysosomal nuclease PLD3 by a novel cell-based assay

Abstract: Phospholipase D3 (PLD3) and phospholipase D4 (PLD4), the most recently described lysosomal nucleases, are associated with Alzheimer’s disease, spinocerebellar ataxia, and systemic lupus erythematosus. They exhibit 5′ exonuclease activity on single-stranded DNA, hydrolyzing it at the acidic pH associated with the lysosome. However, their full cellular function is inadequately understood. To examine these enzymes, we developed a robust and automatable cell-based assay based on fluorophore- and fluorescence-quenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…To correlate the catalytic activity of PLD3 with its PTM status during the course of iNGNs differentiation, a PLD3-specific acid 5′ exonuclease activity assay was carried out ( Cappel et al., 2021 ). Therefore, whole-cell lysates of iNGN cells were incubated with a fluorophore- and quencher-coupled oligodesoxynucleotide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To correlate the catalytic activity of PLD3 with its PTM status during the course of iNGNs differentiation, a PLD3-specific acid 5′ exonuclease activity assay was carried out ( Cappel et al., 2021 ). Therefore, whole-cell lysates of iNGN cells were incubated with a fluorophore- and quencher-coupled oligodesoxynucleotide.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has led to the identification of a large group of protein substrates from different subcellular compartments that are not restricted to the ER, including cytosolic (PFKP, SQSTM1), nucleolar (PPME1), cytoskeletal (TUBB, MAP2), and lysosomal (CTSB, PLD3, and ACP2) proteins ( Broncel et al., 2016 ; Kielkowski et al., 2020a ). In particular, in the lysosome, there is only limited evidence on PTMs of luminal lysosomal proteins other than N-glycosylation amid numerous diseases associated with lysosomal proteins such as the lysosomal acid phosphatase ACP2 in lysosomal storage diseases (LSDs) or the 5′-3′ exonuclease PLD3 in Alzheimer's disease and autoinflammatory diseases ( Cappel et al., 2021 ; Cruchaga et al., 2014 ; Gavin et al., 2021 ; Gonzalez et al., 2018 ; Marques and Saftig, 2019 ; Schultz et al., 2011 ; Stadlmann et al., 2017 ; Stoka et al., 2016 ). Therefore, the discovery of lysosomal protein PTMs might shed new light on the regulation of their function, localization, and protein-protein interactions and hence putatively uncover unknown pathophysiologic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Myelin, a phospholipids, might also be regulated by PLD3. Recently, PLD3 was found to exhibit ssDNA acid 5′ exonuclease activity (Gavin et al, 2018 ; Cappel et al, 2020 ), which was also associated with brain diseases such as Alzheimer's disease and spinocerebellar ataxia (SCA) (Gavin et al, 2018 ). Hence, in our case, the pathological changes in the patient who presented with high intensity white matter may have resulted from PLD3 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the phospholipase D family of enzymes that catalyze the hydrolysis of membrane phospholipids, PLD3 has been proven to be involved in the processing of amyloid-beta precursor protein (Fazzari et al, 2017 ). Recently, two proteins from the PLD family, namely, phospholipase D3 (PLD3) and phospholipase D4 (PLD4), were found to exhibit single stranded DNA (ssDNA) acid 5′ exonuclease activity (Gavin et al, 2018 ; Cappel et al, 2020 ). Previous studies revealed that a heterozygous mutation of PLD3 might increase the risk of Alzheimer's disease and spinocerebellar ataxia (Wang et al, 2015 ; Nibbeling et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some PLD family enzymes (e.g. PLD6, Zucchini, Nuc, and BfiI) exhibit similar biochemical features as PLD3 and PLD4, such as lack of requirement for divalent cations and sensitivity to inhibition by vanadate or tungstate [16]. These enzymes also contain the signature HKD/E motifs.…”
Section: Introductionmentioning
confidence: 99%